Crafting textiles : tablet weaving, sprang, lace and other techniques from the Bronze Age to the early 17th century - Pritchard, Frances (Ancient textiles series, 2021)
"New research into the techniques of tablet weaving, sprang, braiding, knotting and lace is presented in this lavishly illustrated volume written by leading specialists from Austria, Canada, Denmark, France, Germany, Sweden, Switzerland, the UK and USA. Drawing inspiration from the pioneering work of Peter Collingwood, this publication explores aspects of these craft skills in the prehistoric, Roman and medieval world through scientific, object-based analysis and 'research through making'. The work is the outcome of recent discoveries of archaeological textile finds from excavations as well as fresh examination of material recovered in the past, or preserved in treasuries. Early textiles form an increasingly popular subject of interest and this publication, which is a landmark in the study of various specialised textile techniques, aims to provide the reader with a better understanding of these virtuoso craft skills in antiquity"--